Scientific Opinion on the substantiation of health claims related to Saccharomyces cerevisiae var. boulardii CNCM I‐1079 and defence against pathogenic gastro‐intestinal microorganisms (ID 913, further assessment) pursuant to Article 13(1) of Regulation (EC) No 1924/2006 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to provide a scientific opinion on a health claim pursuant to Article 13 of Regulation (EC) No 1924/2006 in the framework of further assessment related to Saccharomyces cerevisiae var. boulardii CNCM I‐1079 and defence against pathogenic gastro‐intestinal microorganisms. The food constituent that is the subject of the health claim, Saccharomyces cerevisiae var. boulardii CNCM I‐1079, is sufficiently characterised. The claimed effect, defence against pathogenic gastro‐intestinal microorganisms, is a beneficial physiological effect. The proposed target population is the general population. The Panel notes that the evidence provided is not sufficient to establish that the strains Saccharomyces cerevisiae var. boulardii CNCM I‐1079 and Saccharomyces cerevisiae var. boulardii Hansen CBS 5926, which were used in the studies provided, are identical, and considers that owing to the possibility that the effects are strain‐specific, results obtained with one strain cannot be extrapolated to another strain. On the basis of the data presented, the Panel concludes that a cause and effect relationship has not been established between the consumption of Saccharomyces cerevisiae var. boulardii CNCM I‐1079 and defence against pathogenic gastro‐intestinal microorganisms.